Hindu Theology in Early Modern South Asia: The Rise of Devotionalism and the Politics of Genealogy, by Kiyokazu Okita - Keune, Jon (Religions of South Asia, 2017)
Hindu Theology in Early Modern South Asia: The Rise of Devotionalism and the Politics of Genealogy, by Kiyokazu Okita. Oxford: Oxford University Press, 2014. xiii + 279 pp., £65.00 (hb), £55.36 (eb). ISBN 978-0-19-870926-8 (hb).